2006
DOI: 10.2117/psysoc.2006.228
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in Old Adults: The Performance on Happe's Stories and Faux Pas Stories

Abstract: Theory of mind abilities in old adults did not receive attention until Happé, Winner, and Brownell (1998) found that the theory of mind performance improved with advancing age. However, Maylor, Moulson, Muncer, and Taylor (2002) and Sullivan and Ruffman (2004) reported that the old adults performed worse than the young adults on theory of mind stories. We used "strange stories" (Happé et al., 1998;Maylor et al., 2002) and faux pas stories (Stone Baron-Cohen, Calder, Keane, & Young, 2003) separately to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 15 publications
6
29
0
4
Order By: Relevance
“…Az idős korosztály teljesítménye a legalacsonyabb a mintán belül az elszólást követő negatív érzelmi következmények, vagyis az affektív mentálisállapot-tulajdonítás tekintetében. Azaz a faux pas megértésének kognitív és affektív komponense is hanyatlik az életkor előrehaladtával, melyek megerősítik az idősekkel kapcsolatos korábbi kutatási eredményeket, miszerint a tudatelméleti teljesítmény romlik az életkor előrehaladtával (Maylor és mtsai, 2002;Duval és mtsai, 2010), illetve hogy specifikusan a Faux Pas Felismerése Teszten elért teljesítmény is alacsonyabb színvonalú időskorban (Wang és Su, 2006). A tudatelmélet időskori teljesítményromlásának kognitív funkcióktól való függetlenségét (Moran, 2013) vagy kapcsolatát a második vizsgálatunk eredményei támaszthatják alá.…”
Section: Az Első Vizsgálat Eredményeiunclassified
See 1 more Smart Citation
“…Az idős korosztály teljesítménye a legalacsonyabb a mintán belül az elszólást követő negatív érzelmi következmények, vagyis az affektív mentálisállapot-tulajdonítás tekintetében. Azaz a faux pas megértésének kognitív és affektív komponense is hanyatlik az életkor előrehaladtával, melyek megerősítik az idősekkel kapcsolatos korábbi kutatási eredményeket, miszerint a tudatelméleti teljesítmény romlik az életkor előrehaladtával (Maylor és mtsai, 2002;Duval és mtsai, 2010), illetve hogy specifikusan a Faux Pas Felismerése Teszten elért teljesítmény is alacsonyabb színvonalú időskorban (Wang és Su, 2006). A tudatelmélet időskori teljesítményromlásának kognitív funkcióktól való függetlenségét (Moran, 2013) vagy kapcsolatát a második vizsgálatunk eredményei támaszthatják alá.…”
Section: Az Első Vizsgálat Eredményeiunclassified
“…A felnőtt tesztváltozat azonban jobban differenciál az életkori csoportok között, míg 11-12 éves kor között teljesítményemelkedés, addig a legidősebb életkorban, a 60-75 évesek korosztályában szignifikáns teljesítményromlás következik be a tudatelméleti teljesítményben, megerősítve a külföldi kutatások eredményeit (Wang és Su, 2006). Az affektív tudatelméleti komponenst mérő Faces Teszt alacsonyabb életkori övezetekben jobban differenciál, míg a serdülőkortól már nem jelez életkori főhatást, utóbbinak elsősorban módszertani okai lehetnek, hiszen plafonhatás érvényesül.…”
Section: Az Első Vizsgálat Eredményeiunclassified
“…Subsequent studies have indicated that ToM abilities are either preserved or decline in older adults. Twelve of these studies have demonstrated a main effect of age on overall task performance on at least one ToM measure, although the use of control conditions and covariates have enabled researchers to attribute some age effects to declines in other cognitive processes rather than a decline specifically related to ToM (Saltzman et aI., 2000;Maylor et aI., 2002;Phillips et aI., 2002;Sullivan & Ruffman, 2004;German & Hehman, 2006;Wang & Su, 2006;Uekermann et aI., 2006;McKinnon & Moscovitch, 2007;Bailey et aI., 2008;Pardini & Nichelli, 2009). Some studies have found that lower ToM ability in older adults compared to younger adults can be accounted for by declines in general cognitive processes such as working memory or executive functioning, rather than ToMspecific declines (Sullivan & Ruffman, 2004;Saltzman et aI., 2000;German & Hehman, 2006;McKinnon & Moscovitch, 2007).…”
Section: Tom and Healthy Agingmentioning
confidence: 99%
“…Some studies have found that lower ToM ability in older adults compared to younger adults can be accounted for by declines in general cognitive processes such as working memory or executive functioning, rather than ToMspecific declines (Sullivan & Ruffman, 2004;Saltzman et aI., 2000;German & Hehman, 2006;McKinnon & Moscovitch, 2007). Other studies have not been able to account for ToM-specific differences with general cognitive processes; they have found evidence of ToM-specific impairment with age on some tasks (Phillips et aI., 2002;Wang & Su, 2006;Uekermann et aI., 2006;Slessor et aI., 2007;Bailey et aI., 2008). Including 3 studies that have had mixed results across different ToM measures, 9 studies have found evidence suggesting that ToM-specific ability is relatively preserved with age (Saltzman et aI., 2000;Sullivan & Ruffman, 2004;MacPherson et aI., 2002;German & Hehman, 2006;Wang & Su, 2006;Keightley et aI., 2006;McKinnon & Moscovitch, 2007;Slessor et aI., 2007;Verdon et aI., 2007), while 9 studies have found evidence suggesting that ToM may decline with age (Saltzman et aI., 2000;Maylor et aI., 2002;Sullivan & Ruffman, 2004;Phillips et aI., 2002;Wang & Su, 2006;Uekermann et aI., 2006;Bailey et aI., 2008;Pardini & Nichelli, 2009).…”
Section: Tom and Healthy Agingmentioning
confidence: 99%
See 1 more Smart Citation